Doxorubicin/Adriamycin Monotherapy or Plus Ifosfamide in First-Line Treatment for Advanced Soft Tissue Sarcoma: A Pooled Analysis of Randomized Trials - Wang, Bi-Cheng; Kuang, Bo-Hua; Xiao, Bo-Ya; Lin, Guo-He (Frontiers in Oncology, 2021)
Background Doxorubicin/Adriamycin (ADM) alone or combined with ifosfamide (IFO) (AI) is available for previously untreated advanced soft tissue sarcoma (ASTS). However, the clinical choice between them remains controversial. In this pooled analysis, we comprehensively compared the efficacy and tolerability of AI versus ADM in patients with ASTS. Methods PubMed, Web of Science, EMBASE, and Cochrane Library were systematically searched from inception to April 14, 2021. Eligible studies were randomized clinical trials comparing AI to ADM. The primary outcomes were overall survival (OS), progression-free survival (PFS), and objective response rate (ORR). Discontinuation rate (DR) and toxic death (TD) were explored as secondary outcomes. Results Overall, three open-label randomized phase 2/3 clinical trials with a total of 1108 newly diagnosed ASTS patients were enrolled. Between AI and ADM, pooled hazard ratios were 0.93 (95% confidence interval 0.58-1.50, p = 0.78) for OS and 0.85 (0.57-1.25, p = 0.41) for PFS. While pooled risk ratios for ORR, DR, and TD were 1.37 (0.94-1.99, p = 0.10), 1.04 (0.74-1.46, p = 0.82), and 0.68 (0.19-2.36, p = 0.54) respectively. No publication bias was observed across the studies. Conclusion In the first-line setting, adding IFO to ADM failed to benefit ASTS patients against ADM alone, even with comparable tolerability.